Enhanced Wireless Control of Anti-Theft Solar Photovoltaic Modules Using Tree Topology - Florence Choong Chiao Mei; Jia Jun, Kang (Journal of Advanced Industrial Technology and Application, 2024)
The increase in the market value of photovoltaic modules resulted in a growing number of solar panel thefts, causing tremendous losses to the owner of the solar farm. As a result, huge investments are needed to secure these solar panels. The current solution of using CCTV cameras and sensors requires high computational power, is expensive, and requires personnel to monitor it. This paper proposes an energy-efficient and cost-effective wireless encryption anti-theft solar photovoltaic system utilizing a radio frequency transceiver and a tree topology. The tree topology overcomes the limitation of a radio frequency transceiver by allowing a higher number of transmissions to be done simultaneously. A gyroscope module is used to detect theft by reading the rotational speed of the solar panel. Using the tree topology, the child node can transmit an error signal to the master node before calling the owner. The master node of the solar farm is responsible for transmitting a password to every child node to decrypt the circuit. If one of the solar panels is stolen, the circuit of the stolen panel will be encrypted if the password is not received within three minutes. A lithium-ion battery and a battery charger module are installed for energy storage to allow the system to operate in the absence of sunlight. The proposed system yielded a 39.3% reduction in power consumption and is a promising method for large-scale implementation in solar farms.